A produção de histórias em quadrinhos digitais no ensino-aprendizagem de língua inglesa - Santos Júnior, Israel Domingos dos (2022)
The English language is present in most education systems in the world. However, there is a need for considerable changes in the teaching and learning of English, so that pedagogical practices can make it increasingly relevant and effective. The research question seeks to investigate how the production of digital comics can contribute to the teaching and learning of the English language. The research aims to propose the production of digital comics as a possibility to develop writing and orality skills in the teaching and learning of the English language, through a didactic sequence, which includes the realization of a digital comic book production workshop, through Mobile Learning, in addition to the analysis of students' productions, according to some indicators of communicative skills of the National Common Curriculum Base. This work is based on teaching and learning of English language anchored by the Communicative Approach and Meaningful Learning; in comics as an educational resource; in a proposal of multiliteracies: linguistic, literary and digital; in Mobile Learning as an active methodology; in the didactic sequence to direct the pedagogical actions and in the results obtained in the systematic literature review developed by this researcher. The participants come from three classes of the ninth grade of Elementary School, from a municipal public school, totaling 77 students, aged between 14 and 17, with whom the researcher works as an English language teacher. The research is qualitative, dialectical, empirical, interventionist, through action research. It was developed through a workshop for the production of digital comics, mediated by a didactic sequence, with a view to raising awareness of the comics genre, establishing a profile of the participants and using instruments to gather information, such as some questionnaires and conversation circles. From the analysis of the data collected through the initial free productions of comics, the productions of digital comics, some questionnaires and activities to raise awareness of the comics genre and self-assessment, it was verified the feasibility of using the production of digital comics, in English, contributing to the development of multiliteracies, favoring creativity, motivation, construction of a lexical repertoire and moments of discussion, in addition to meeting indicators of competences and abilities, suggested by the National Common Curriculum Base.